Preparation of Ion Exchange Membrane Chromatography by Modification of Polyethersulfone Membrane Through UV Grafting of [2-(Acryloyloxy) Ethyl] Trimethyl Ammonium Chloride and Acrylic Acid Monomer - Wan Najibah, Mohamad (2013)
Chromatographic separation of protein mixtures has become one of the most effective widely used means of techniques to purifying individual proteins. Packed bed chromatography is the common technique that is used configuration for the protein separation. However, packed bed chromatography has its some limitations during separation process such as high pressure drop and time consuming. Membrane chromatography then introduced to overcome the limitations of the packed bed chromatography. In the current research, polyethersulfone (PES) commercial membrane was converted into ion exchange (IEX) membrane chromatography by attaching [2-(acryloyloxy)ethyl] trimethyl ammonium chloride (AETMA) and acrylic acid (AA) monomer using UV light irradiation technique. The effect of AETMA and AA monomer concentration from 1.5 M to 2.0 M was studied. The IEX membrane was characterized in term of degree of grafting, changed of functional group as well as protein binding capacity using pure bovine serum albumin. For AETMA-grafted membrane, the binding capacity increase about the 65.32 % as the monomer concentration increase from 1.5 M to 2.0 M. While, for AA-grafted membrane, the binding capacity shows a huge increment when the monomer concentration was increase from 1.5 M to 2.0 M with amount 78.65 %.